Movie success in a genre specific contest: Evidence from the US film industry - Daniel Kaimann; Julia Pannicke (Technische Universität Ilmenau, Institut für Volkswirtschaftslehre, 2015)
This article examines the economic effect of computer animation movie success by using data from all widely released feature length movies between 2011 and 2014, and all computer animated movies in North America between 1995 and 2014. We show that computer animated movies successfully attract families, parents, children, and teenagers and outperform other major movie genres (e.g., action, com-edy or drama). This research sample also provides initial evidence that, counter to industry thinking in the film business, stardom is not directly associated with movie success.
Keywords: C31; L10; L82; M21; 330; motion pictures economics; movie genre; computer animated movies